Factors Affecting The Implementation Of Quality Programs In Telekom Malaysia A Study On The Effectiveness Of Quality Improvement Projects - Abd Razak, Abd Halim (2001)
The study is to assess the effectiveness of the quality initiatives by looking at factors affecting the success of the quality programs. The quality programs refer particularly to the QCC/QIT implementation.